Modifications of the C terminus Affect Functionality and Stability of Yeast Triacylglycerol Lipase Tgl3p - Koch, Barbara (American Society for Biochemistry and Molecular Biology, 2014)
Lipid droplets are specific organelles for the storage of triacylglycerols and steryl esters. They are surrounded by a phospholipid monolayer with a small but specific set of proteins embedded. Assembly and insertion of proteins into this surface membrane is an intriguing question of lipid droplet biology. To address this question we studied the topology of Tgl3p, the major triacylglycerol lipase of the yeast Saccharomyces cerevisiae, on lipid droplets. Employing the method of limited proteolysis of lipid droplet surface proteins, we found that the C terminus of Tgl3p faces the inside of the organelle, whereas the N terminus is exposed at the cytosolic side of lipid droplets. Detailed analysis of the C terminus revealed a stretch of seven amino acids that are critical for protein stability and functionality. The negative charge of two aspartate residues within this stretch is crucial for lipase activity of Tgl3p. A portion of Tgl3p, which is located to the endoplasmic reticulum, exhibits a different topology. In the phospholipid bilayer of the endoplasmic reticulum the C terminus faces the cytosol, which results in instability of the protein. Thus, the topology of Tgl3p is important for its function and strongly dependent on the membrane environment.